Kuliah kewirausahaan, berpengaruhkah pada minat Berwirausaha? - Rintasari, Nugraheni; Hidayat, Effan (PERWIRA - Jurnal Pendidikan Kewirausahaan Indonesia, 2019)
This study aims to examine the effect of entrepreneurship courses, income expectations, and entrepreneurial characteristics on entrepreneurial interest. The object of the research was student participants in the Ahmad Dahlan University Accountant concentration class who had taken six courses related to Entrepreneurship. The number of respondents was 53. The results showed that entrepreneurship courses, income expectations, and the characteristics of entrepreneurship explained 37.2% of the factors affecting entrepreneurial interest. Hypothesis testing using the regression test shows the results that college entrepreneurship and income expectations influence the interest in entrepreneurship and the characteristics of entrepreneurship have no effect. This shows that universities have the opportunity to cultivate curriculum related to entrepreneurship. Because there are indications that the interest in entrepreneurship can be grown through entrepreneurship courses.